Enhanced Oviposition Preferences and Larval Performance of Hermetia illucens L. in Fruit Wastes Fermented by Effective Microorganisms - Rahayu, Resti; Jannatan, Robby; Ronaldo, Muhamad; Muslima, Risa Ukhti (UI Scholars Hub, 2025)
Organic waste comprises a considerable portion of global waste, requiring effective management. The ability of the black soldier fly (Hermetia illucens, BSF) to convert organic waste into biomass has been well reported. However, bioconversion can be hindered by fiber-rich substrates, a challenge that can be addressed through substrate pretreatment. This study examined the oviposition preferences and larval performance of BSFs in several fruit wastes fermented by effective microorganisms (EMs), which were compared to non-fermented substrates. The oviposition attractants utilized pineapple peel and overripe soursop, with larval performance evaluated among different treatments, i.e., non-fermented pineapple peel (NFP), fermented pineapple peel (FP), non-fermented pineapple peel plus coconut endosperm waste (NFPC), and fermented pineapple peel plus coconut endosperm waste (FPC). Measured parameters included larval biomass, substrate consumption, the waste reduction index (WRI), and adult emergence. The result indicated that fermented pineapple peel produced the highest number of eggs among the oviposition attractant treatments. Larval biomass was highest in FP, while substrate consumption, WRI, and adult emergence rates were comparable between FP and FPC. Overall, the fermented substrates outperformed the non-fermented substrates across all parameters. These findings confirmed that fermentation with EMs enhances the utilization of fruit waste as an oviposition attractant and improves the performance of BSF bioconversion.